Ranma 1/2. Vol. 33 - Takahashi, Rumiko, 1957- (Viz Media, 2006)
While traveling, the Tendo and Saotome families have to take shelter in a strange mansion haunted by a beautiful young girl who died before her first date. When girl-type Ranma looks into a large mirror, the spirit of the girl escapes the mirror as a copy of Ranma, determined to experience love at last.